THE EFFECTIVENESS OF STORY TELLING TO IMPROVE STUDENT’S SPEAKING SKILLS AT THE TENTH GRADE OF SMA GAJAH MADA BANDAR LAMPUNG - Exglard, iradnaluwiner (Universitas Samudra, 2024)
Speaking is the first method for communicating with people in a social group. The storytelling technique helps students' speaking skills abilities by expanding their vocabulary, developing creativity, improving pronunciation, and organizing thoughts. This study aims to 1) determine whether Storytelling is compelling to speaking skills in the tenth grade of SMA Gajah Mada Bandar Lampung and 2) to understand how the storytelling method is applied in learning English in class X SMA Gajah Mada Bandar Lampung. This research used quantitative research as